Social Skills Training as a Psychosocial Intervention to Improve Social Functioning in Schizophrenia: A Literature Review - Suhermi Suhermi; Amin Samiasih; Muhammad Fatkhul Mubin; Vivi Yosafianti; Ratih Sri Wardani (Indonesian Journal of Global Health Research, 2026)
Social functioning is an individual's ability to interact adaptively, perform social roles, and engage in social activities in accordance with prevailing norms. In patients with schizophrenia, social functioning often declines due to cognitive, affective, and motivational impairments that accompany the course of the illness. This systematic review aims to evaluate the effectiveness of Social Skills Training interventions in improving various aspects of social functioning, including communication skills, social interaction, social roles, and participation in social activities. This review follows the PRISMA-2020 guidelines. A systematic search was conducted on the Scopus, PubMed, ProQuest, ScienceDirect, and EBSCO databases for English-language studies published between 2021 and 2025. A combination of keywords was used to form the search string, including “Social Skill Training” OR “SST” AND “Social functioning” OR “interpersonal functioning” OR “social performance” AND “Schizophrenia”. Boolean operators ‘AND’ and “OR” were used to narrow the resultsQuality assessment was conducted independently using the Joanna Briggs Institute (JBI) checklist. The synthesis of the five research articles analyzed showed that Social Skills Training (SST) had a positive impact on improving the social functioning of schizophrenia patients in various service contexts and patient characteristics. The studies reviewed consisted of two studies with a Randomized Controlled Trial (RCT) design and three quasi-experimental studies, with sample sizes varying from small to medium. All studies reported an increase in social functioning after the provision of SST intervention, either as a single intervention or in combination with standard therapy. Social Skills Training (SST) has been proven effective in improving the social functioning of schizophrenia patients, including communication skills, social interaction, social roles, and participation in social activities.